(untitled) (Fiep Bulletin - online, 2015)
The objective of this study is to contribute with the discussions on the formation of the teacher of Physical Education and the interdisciplinary pedagogical practice on the school organized by cycles of formation in the City of Porto Alegre Education Network. On the politic-pedagogical proposition focused on the education by cycles what moves the pedagogical action is the interdisciplinary practice. A practice centered in collective action with the objective of creating a rupture with the fragmentation of knowledge and promoting a deeper understanding of the reality of the world, from a closer reading of the student context and expanding to a global context. The methodology of this study is characterized by a qualitative ethnographical research, and the instruments used were the participant observation (registered in field diary), semi-structured interviews and document analysis. The formation of the collaborative teachers was marked by a technical and instrumental teaching model. During this period of formation they were rarely stimulated to think about interdisciplinary education (or aware of their responsibility subjects producers of interdisciplinary knowledge), along undergraduation the teachers went through a situation of passiveness, of receptors of elaborate knowledge. They did not live practices of interdisciplinary education and were not prepared to work in an interdisciplinary way. Thus, we understand that the professional formation course of these teachers reflects, afterwards, on its pedagogical practice. In this sense there is a need to rethink the formation of the teachers of Physical Education to act interdisciplinary.